Evaluation of The Rationality of Hypertension Medication Use in Puskesmas Central Cimahi - Faizal Hermanto; Anna Choirunissa; Titta Hartyana Sutarna; Riza Amelia; Akmal Rizwan (Postgraduate, University of Mataram, 2024)
A persistent and abnormal increase in blood pressure in the arteries is known as hypertension (HT. This research aims to assess the consumption of antihypertension at the Puskesmas Central Cimahi. Non-analytical descriptive methods were used in this investigation. Retrospective data was collected by accessing patient prescriptions and medical record data. Fifty-six patient samples in this study met the inclusion requirements. Quantitative and qualitative methods are used to evaluate rationality. Quantitative data analysis is processed to determine the number of patients, gender, age, and type of drug classification. Qualitative data analysis is processed to evaluate the appropiate of the indication, drug, patient and dose. Based on the research results, 52 people suffered from stage 1 hypertension, and four patients suffered from stage 2 hypertension. Amlodipine monotherapy was the most frequently prescribed drug, namely 92%. While the combination of amlodipine, captropil, amlodipine, and hydrochlorothiazide amounted to 4%. The rationality of treating hypertensive patients who meet the right indications, the right drug, the right patient and the right dose is 100%. It can be concluded that the evaluation and use of hypertension medication at the Puskesmas Central Cimahi as a whole meets the criteria for rational treatment.